Malfunction Analysis of Cylindrical Gear Reducer Used in Axial Flow Fan of Direct Air Cooled System - Liu Haidong; Li Qin (Jixie chuandong)
The malfunction detection cylindrical gear reducer used in axial flow fan of direct air cooled system and the calculation analysis of the reducer key part containing gear,shaft and bearing are carried out.The result display that gear strength low and excessive shaft bending brings the problem of the tooth surface load maldistribution and additional dynamic load,bearing life low and so on.According to current problem,the technical improve proposition is suggested.